Political Culture and Christian Trade Unionism: The Case of Belgium - Barnes, Samuel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1964)
SummaryBelgian trade unionism has always intensely attracted industrial relations specialists because of some peculiarities in its structuring and functioning. The object of the following paper is to impart some knowledge about the history of pluralist Belgian trade unionism, its foundation and relationships it entertains at different levels: religious, political, ideological.